Abundance analysis of APOGEE spectra for 58 metal-poor stars from the bulge spheroid. Issue 3 (1st August 2022) - Razera, R; Barbuy, B; Moura, T C; Ernandes, H; Pérez-Villegas, A; Souza, S O; Chiappini, C; Queiroz, A B A; Anders, F; Fernández-Trincado, J G; Friaça, A C S; Cunha, K; et al.
ABSTRACT: The central part of the Galaxy hosts a multitude of stellar populations, including the spheroidal bulge stars, stars moved to the bulge through secular evolution of the bar, inner halo, inner thick disc, inner thin disc, as well as debris from past accretion events. We identified a sample of 58 candidate stars belonging to the stellar population of the spheroidal bulge, and analyse their abundances. The present calculations of Mg, Ca, and Si lines are in agreement with the ASPCAP abundances, whereas abundances of C, N, O, and Ce are re-examined. We find normal α-element enhancements in oxygen, similar to magnesium, Si, and Ca abundances, which are typical of other bulge stars surveyed in the optical in Baade's Window. The enhancement of [O/Fe] in these stars suggests that they do not belong to accreted debris. No spread in N abundances is found, and none of the sample stars is N-rich, indicating that these stars are not second generation stars originated in globular clusters. Ce instead is enhanced in the sample stars, which points to an s-process origin such as due to enrichment from early generations of massive fast rotating stars, the so-called spinstars.